KESADARAN DIRI PETANI DALAM MENERAPKAN KONSEP URBAN FARMING PADA PERTANIAN DI PERKOTAAN DI KABUPATEN PURWOREJO (Farmers' Self-Awareness in Applying the Concept of Urban Farming on Urban Agriculture in Purworejo District) - KUSUMANINGRUM, ARTA; WICAKSONO, ISTIKO AGUS; WIDIANTONO, DIDIK (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
The objectives of this research were: 1) To determine the characteristics of farmers in applying the Urban Farming concept to urban agriculture in Purworejo Regency, 2) To determine the level of self-awareness of farmers in applying the Urban Farming concept to urban agriculture in Purworejo Regency, and 3) To determine What are the benefits of farmers in applying the Urban Farming concept to urban agriculture in Purworejo Regency? This research was descriptive and class interval. The number of samples in this research was 30 farmers. The results of this research showed: 1) The characteristics of farmers in applying the urban farming concept to agriculture in urban areas in Purworejo Regency was high school farmer education with a percentage of 54%. Farmer experience: less than 10 years, with a percentage of 77%. Age 50-60 years with a percentage of 40%. Land area less than 500 m was 74%. The majority of plants cultivated were ornamental plants, as much as 30%, 2) Farmers' self-awareness in implementing the urban farming concept is at the highest percentage, namely 94.74% that farmers know that food can be obtained from urban farming activities, 3) and the last, in implementing urban farming in urban areas in Purworejo Regency, farmers use verticulture, plant racks, tabulampots, house fences, house walls, hanging pots, hydroponics, and used bottles.